Adaptive quasi-sliding mode control based on a recursive weighted least square estimator for a DC motor - Minchala Ávila, Luis Ismael (2016)
This paper presents the methodology of design of a discrete-time adaptive quasi-sliding mode controller (QSMC) based on a recursive weighted least square (RWLS) estimator for a dc motor. The proposed control scheme allows handling the classic problem of a QSMCs, which is the steady-state error due to the use of a saturation function instead of a switching function in the sliding mode control (SMC) algorithm. The use of linear and nonlinear signal references helps to show the closed-loop performance of the control system and its tracking capabilities. Experimental results show a better performance of the RWLS-QSMC algorithm applied on the speed control of a dc motor than a classic SMC.